Desain Kelembagaan Satuan Pengawas Internal (SPI) di STAIN Curup (Sebuah Penawaran Desain SPI Untuk Efektivitas Dan Efisien Pengelolaan Keuangan, Kinerja Pegawai Dan Aset Negara) - Sugiatno, Sugiatno (Institut Agama Islam Negeri (IAIN) Curup, 2018)
Internal Supervisory Unit (SPI) is a quality assurance unit that exist in every Islamic University. Internal Supervisory Unit (SPI) STAIN Curup is an element of supervisor who performs non-academic field supervision functions for and on behalf of University Leaders. The scope of non-academic field supervision includes: (1) finance, (2) asset, and (3) human resources (HR). After the establishment of the internal supervisory unit (SPI) at STAIN Curup since september 2017 ago until now has not been able to perform its functions to conduct internal supervision and audit. Since the institutional or organizational structure does not have organizational structure, vision and mission, authority and responsibility and lack of internal auditor performance guidance to be conducted in the framework of evaluation of non-academic field activities including audit planning activities, testing and evaluating information, audit result notification and acts further audit results. This type of research is field research (fileld research), in this case the researcher uses descriptive qualitative research type that is analyzing and presenting the facts systematically based on the number or amount of data mendepenelitiankan in the form of data for the understood and concluded. this research is comparative descriptive research in the form of concept study. From the aspect of the objectives, this research is a study that attempted to describe the substance of the analysis of the concept of the formulation of the Design of Institution of Internal Control Unit (SPI) at STAIN Curup (an SPI design offer for effectiveness and efficient financial management, employee performance and state assets). The result of this research is: The existence of Internal Supervisory Unit at STAIN Curup is a must again after the issuance of Regulation of the Minister of Religious Affair No. 25 year 2017 dated 04 August 2017 about Internal Supervisory Unit (SPI) at State Religious College. The design of vision, mission, purpose, function, authority, and Structure of STAIN Curup has been formulated based on the FGD and KMA results dated 04 August 2017. Internal Auditor Performance Internal Audit Unit (SPI) STAIN Curup can be seen from four audit execution, namely: a ). Audit planning stage, b). Testing and evaluation phase of information, c). Stage of delivery of audit result, d). Follow-up phase of audit.